2019
DOI: 10.1155/2019/4541797
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells from the Epidermis and Dermis of Psoriasis Patients: Morphology, Immunophenotype, Differentiation Patterns, and Regulation of T Cell Proliferation

Abstract: Psoriasis is a skin disease characterized by hyperproliferation of keratinocytes and chronic inflammation. Mesenchymal stem/stromal cells (MSCs) exhibit an immunoregulatory function that can be altered in the skin of these patients. However, to date, the presence and functional capacity of MSCs in the dermis and epidermis of patients with psoriasis have not been fully established. In the present study, we evaluated the presence of MSCs in the skin of patients by obtaining adherent cells from the dermis and epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…7 A recent work demonstrated that skin MSCs from patients with psoriasis have low differentiation capacity, high human leucocyte antigen-I expression levels and low immunoregulatory capability. 8 Lymphocyte inhibition seems to be compromised in psoriatic skin, mainly because of dermal MSCs, leading to abnormalities in cytokine secretion through circular RNA. 9,10 Moreover, MSCs from psoriatic plaques have been shown to promote keratinocyte proliferation, with subsequent abnormal thickening of the epidermis.…”
Section: Mesenchymal Stem Cells In Psoriasismentioning
confidence: 99%
“…7 A recent work demonstrated that skin MSCs from patients with psoriasis have low differentiation capacity, high human leucocyte antigen-I expression levels and low immunoregulatory capability. 8 Lymphocyte inhibition seems to be compromised in psoriatic skin, mainly because of dermal MSCs, leading to abnormalities in cytokine secretion through circular RNA. 9,10 Moreover, MSCs from psoriatic plaques have been shown to promote keratinocyte proliferation, with subsequent abnormal thickening of the epidermis.…”
Section: Mesenchymal Stem Cells In Psoriasismentioning
confidence: 99%
“…Therefore, there is increasing interest in improving the efficiency of differentiation into osteoblasts for bone regeneration. Several studies were reported on the isolation and culture of MSCs using various tissues including bone barrow [ 16 , 17 , 18 , 19 ]. However, BM-MSCs have lower proliferation and differentiation capacity than other sources of stem cells and show a small number of cells and donor-age-dependent characteristics [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, BM-MSCs have lower proliferation and differentiation capacity than other sources of stem cells and show a small number of cells and donor-age-dependent characteristics [ 20 ]. Recently, many studies have been conducted on the source of MSCs that can replace bone marrow, and it has been reported that mesenchymal stem cells can be obtained from many tissues, including skeletal muscle, dermal skin, and adipose tissue [ 17 , 18 , 19 ]. Additionally, MSCs from skeletal muscle, dermal skin, and adipose tissue were reported for the presence of osteoblast differentiation capacity [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an increasing interest in improving the efficiency of differentiation into osteoblasts for bone regeneration. Several studies were reported on the isolation, and culture of MSCs using various tissues including bone barrow [12][13][14][15]. However, BM-MSCs have lower proliferation and differentiation capacity than other sources of stem cells and show a small number of cells and donor-age-dependent characteristics [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, BM-MSCs have lower proliferation and differentiation capacity than other sources of stem cells and show a small number of cells and donor-age-dependent characteristics [16]. Recently, many studies have been conducted on the source of MSCs that can replace bone marrow, and it has been reported that mesenchymal stem cells can be obtained from many tissues including skeletal muscle, dermal skin, and adipose tissue [13][14][15]. Additionally, MSCs from skeletal muscle, dermal skin, and adipose tissue were reported for the presence of osteoblast differentiation capacity [17][18][19].…”
Section: Introductionmentioning
confidence: 99%